The impact of radiation dose variability on the response of radiophotoluminescence glass dosimeters – an experimental approach - Manny Mathuthu; Samuel O.O. John; Dithole H. Seepamore; Vincent Maselesele (South African Journal of Science)
The dosimetric properties of radiophotoluminescence glass dosimeters (RPLGDs) make them valuable tools for accurately measuring doses in various radiation fields. Over the years, thermoluminescence dosimeters have been used for both personal and environmental monitoring in South Africa, although they have certain limitations. We investigated the exceptional properties of RPLGDs by characterising their response to different radiation doses, using radiation sources of 60Co, 137Cs, and 241Am. The objective was to assess the ability of RPLGDs to be read multiple times without losing the original signal, and to explore their potential to replace TLDs in diverse radiation environments. A substitution method was employed to determine the reference measurements across all radiation source set-ups. In this approach, the RPLGD, serving as the unit under test, was exposed to the same dose as the ionisation chambers, which acted as reference detectors to accumulate the radiation signal, which was then corrected to determine the air kerma and absorbed dose to water. All relevant corrections affecting the unit under test response were applied to the final readings to characterise the RPLGDs, which were compared with the prescribed dose. The findings of this research are valuable to medical facilities and radiation workers as they offer both technical and economic benefits through improving the accuracy and reliability of radiation dose monitoring.